2018
DOI: 10.29333/ejgm/93445
|View full text |Cite
|
Sign up to set email alerts
|

Transitional care model: managing the experience of hospital at home

Abstract: Introduction: Design and use of effective strategies to improve care and achieve better results for patients with chronic diseases, reduce the frequency and cost of hospitalization is necessary for these patients. Transitional care model is a new model that have been effective in meeting the needs of these patients. The aim of this mini review study is investigating and describing the various aspects of transitional care model, benefits and core components. Design: The present investigation is a mini review st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 18 publications
1
17
0
3
Order By: Relevance
“…Moreover, the nurses' attitude increased with increasing the level of knowledge (30)(31)(32)(33)(34). The result of this study was consistent with that of the present study (35)(36)(37)). The results of the study conducted by Steenaart (2019) also showed that the use of new educational methods can increase the knowledge and attitude of nurses in the area of organ donation, which was consistent with the results of this study (38)(39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the nurses' attitude increased with increasing the level of knowledge (30)(31)(32)(33)(34). The result of this study was consistent with that of the present study (35)(36)(37)). The results of the study conducted by Steenaart (2019) also showed that the use of new educational methods can increase the knowledge and attitude of nurses in the area of organ donation, which was consistent with the results of this study (38)(39)(40)(41)(42).…”
Section: Discussionsupporting
confidence: 93%
“…Seeking the truth in ambiguous situations is an iterative process, and the educators should create the opportunities for students to repeat and reflect on choices and decisions (94). In order to facilitate practical wisdom, nursing ethics educators should themselves display virtuous character trait inspiring students to follow them as role models (114)(115)(116). The existence of role models is one of the most effective ways to teach values to students (93) .…”
Section: Discussionmentioning
confidence: 99%
“…Transitional care extended beyond hospital discharge has shown to be effective at improving the discharge process, reducing length of hospital stay and improving patient outcome post-discharge (Alper et al, 2020;Coleman, 2003;Mazanec et al, 2018). Transitional care model with managed care approach played an important role in improving and promoting health (Naylor & Keating, 2008), reducing health care utilization and cost and improving patient satisfaction and quality of life (Rezapour-Nasrabad, 2018). Older patients with multiple comorbidities and complex therapeutic regimes, as well as their caregivers, are particularly vulnerable to breakdowns in care and thus has the greatest need for transitional care (Naylor & Keating, 2008).…”
Section: Transitional Carementioning
confidence: 99%